1988
DOI: 10.1177/0265407588054002
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Three Expected Intimate Relationship States: Commitment, Maintenance and Termination

Abstract: The purpose of the study was to assess which of a group of relationship characteristics discriminate among the following relationship states in heterosexual dating couples: (a) expected commitment state (ECS), (b) expected maintenance state (EMS) and (c) expected termination state (ETS). Data were collected by mailed questionnaires from 37 male and 78 female students randomly selected from a western Canadian university. Results indicate that the expected termination state is the most predictable of the three s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Other recent studies have also supported this particular relationship (Dyer & Halford, 1998;Kingsbury & Minda, 1988;Meeks et al, 1998;Prager, 1989;Sprecher et al, 1995). These ® ndings are also evident in gay relationships (e.g.…”
Section: Introductionsupporting
confidence: 71%
“…Other recent studies have also supported this particular relationship (Dyer & Halford, 1998;Kingsbury & Minda, 1988;Meeks et al, 1998;Prager, 1989;Sprecher et al, 1995). These ® ndings are also evident in gay relationships (e.g.…”
Section: Introductionsupporting
confidence: 71%
“…Although commitment is typically considered to be distinct conceptually from love (Fehr, 1988; Kelley, 1983) and satisfaction (Lewis & Spanier, 1979; Rusbult, 1980), some scholars include it as a characteristic of love (e.g., Sternberg, 1986). Finally, commitment is frequently equated with relationship status or length (Bailey & Helm, 1974; Jedlicka, 1975; Kingsbury & Minda, 1988; Sabatelli & Cecil-Pigo, 1985), thereby potentially obscuring the distinction between commitment as a process and its consequences.…”
Section: Evaluation Of the Literature On Marital Commitmentmentioning
confidence: 99%
“…A wide variety of studies have investigated differences between women and men concerning perceptions of relational de-escalation. Kingsbury and Minda (1988) showed that women report more concern about social, intellectual, and perceived sexual intimacy in declining relationships. Other research concluded that men tend to initiate relationships but that women terminate them (Hill et al, 1976;Rubin, Peplau, & Hill, 1981), that women are more adept than men at monitoring the state and quality of intimate relationships (Bloom & Caldwell, 1981;Hagestad & Smyer, 1982;Hill et al, 1976) and that women anticipate dissolution more quickly than men do (Rubinet al, 1981).…”
Section: And Using De-escalating Meta-mopsmentioning
confidence: 99%